NON-TRADABLE GOODS IN CATCHING-UP EUROPEAN COUNTRIES – AN INSTITUTIONAL PUZZLE? - Saroch, Stanislav; Zd’arek, Vaclav (European Scientific Journal, ESJ, 2015)
This text aims to shed more light on the problem of delays and divergence tendencies in the process of real convergence compared to price level convergence in the case of publicly funded and governed goods and services (merit goods) in selected new EU member states. Since this topic is only briefly overviewed in Égert (2007), whose study focuses mainly on market goods and services, this text examines changes in real volumes and price levels for non-market goods and services. Given data limitation and regional heterogeneity, the focus is on the period between 1999 and 2012 and four selected CEE countries (the Visegrad group). Our preliminary results reveal that there were at least two (three) main tendencies similar across the group of countries during the aforementioned period: a rapid catching up process in the pre-EU period (both real and nominal convergence), some sort of an ‘EU effect’, followed by differentiation resulting from heterogeneous impacts of the on-going sovereign debt (financial) crisis on the chosen group of CEE countries.